2006
DOI: 10.1111/j.1600-0625.2006.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐steroidal anti‐inflammatory drugs selectively inhibit cytokine production by NK cells and γδ T cells

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are known to be risk factors for a systemic inflammatory syndrome in viral infections. Innate immune cells are likely to represent the preferential targets for the deleterious effects of NSAIDs in patients with viral infections. We therefore examined whether various classes of NSAIDs could selectively inhibit cytokine production by innate immune cells. NSAIDs selectively inhibited interferon (IFN)-gamma and tumor necrosis factor (TNF)-alpha production by natural k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 37 publications
1
18
0
1
Order By: Relevance
“…In fact, recent studies showed that NSAIDs selectively inhibit IFN‐γ and TNF‐ α production in spleen cells Michelin et al . (2005) and natural killer (NK) and γδT cells (Inaoka et al , 2006). However, the high lethality after NSAID treatment could be related to a marked systemic increase in TNF‐α production in a situation analogous to that observed in T. cruzi ‐infected C57BL/6 (Pinge‐Filho et al , 1999) and IL‐10 −/− mice (Hunter et al , 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, recent studies showed that NSAIDs selectively inhibit IFN‐γ and TNF‐ α production in spleen cells Michelin et al . (2005) and natural killer (NK) and γδT cells (Inaoka et al , 2006). However, the high lethality after NSAID treatment could be related to a marked systemic increase in TNF‐α production in a situation analogous to that observed in T. cruzi ‐infected C57BL/6 (Pinge‐Filho et al , 1999) and IL‐10 −/− mice (Hunter et al , 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the inhibition of prostaglandin production observed in our studies did not induce alterations in the production of IL-4 in BALB/c infected with T. cruzi, but might have inhibited the development of protective Th1 response in C57BL/6 mice. In fact, recent studies showed that NSAIDs selectively inhibit IFN-g and TNF-a production in spleen cells Michelin et al (2005) and natural killer (NK) and gdT cells (Inaoka et al, 2006). However, the high lethality after NSAID treatment could be related to a marked systemic increase in TNF-a production in a situation analogous to that observed in T. cruzi-infected C57BL/6 (Pinge-Filho et al, 1999) and IL-10 À/À mice (Hunter et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that inhibition of prostaglandin production in C57BL/6 mice inhibited the development of protective Th1 response. In fact, nonsteroidal anti-inflammatory drugs (NSAIDs) selectively inhibit IFN-γ and TNF-α production in spleen cells (Michelin et al, 2005), natural killer (NK) and γδT cells (Inaoka et al, 2006).…”
Section: Role Of Prostaglandins In the Pathogenesis Of Chagas Diseasementioning
confidence: 99%
“…Inaoka et al 4 went on to examine whether NSAIDs could selectively inhibit cytokine production by innate immune cells; they found that early IFN-γ production by innate immune cells, the most efficient strategy for antiviral defence, was impaired by NSAIDs. They concluded that it was possible that the frequent use of NSAIDs during viral infections may cause an overexuberant acquired immune response to the virus to compensate for the decreased antiviral innate immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…However, they are also known to have immunosuppressive properties and are a risk factor for development of the systemic inflammatory response syndrome in viral infections 4 5. These cases highlight two examples where NSAID abuse may have been a significant factor in the development of severe pneumonitis secondary to H1N1 influenza.…”
Section: Introductionmentioning
confidence: 99%